KINETIKA REAKSI POLIESTERIFIKASI GLISEROL ASAM ADIPAT (Kinetics of Polyesterification of Glycerol with Adipic Acid) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The polyesterification of glycerol with adipic acid is a condensation polymerization, in which carboxylic acid react with hydroxyl group. This polymerization produces linear and branch chains because adipic acid has two carboxyl groups and glycerol has three hydroxyl groups. This research was intended to study the kinetics of polyesterification with two variables : temperature and reactant ratio. This research proposed two models : model for ideal system ( based on Florry Theory ) and model II for non-ideal system ( based on Gee and Tre boar Theory ). Model II used activity concept and the activity coefficient was predicted with Modified UNIFAC method. Experiment was carried out in a three necked flask as a batch reactor equipped with a magnetic stirrer, thermometer, and a jacket heater. Adipic acid was charged into the reactor and heated to the desired temperature, then glycerol was added and stirred rigorously. The reaction was carried out in a vacuum condition and nitrogen was bubbled through the reaction mixture. Sample was taken at certain time to determine the COON concentration by titration. The effect of temperature was investigated at mole ratio COOH:OH of 1.5 with temperature range of 130°C-180°C (10°C interval). The effect of mole ratio COOH:OH was investigated at constant temperature of 160°C with mole ratio range of 1.0-3.0 ( 0.5 interval ). Model I and model II could predict well the kinetics of polyesterification of glycerol with adipic acid. Beside that, model II could predict the molecular weight distribution. It can be